(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
The current study aims to evaluate the marginal adaptation of MTA and Bioceramic, using Scanning Electron Microscope in pulpotomized primary molars. Ten extracted primary molars for orthodontic reasons (caries-free or not) were studied and randomally distributed into two groups. Pulpotomy was conducted using either MTA or Bioceramic, the teeth were then restored with composite resin. The crowns were resected longitudinally (bucco-lingual direction) into two halves. The teeth were thermocycled to 200 rounds between 5° and 55°C in distilled water, with 30s dwell time in each bath, the samples were mounted on an aluminum stub and marginal gaps were examined and recorded in micron using Scanning Electric Microscope (SEM) The results showed variable gaps observed between the used materials and the dentinal walls. The gap sizes of MTA material ranged from (4 to 19 micron) and it had the largest mean gaps (mean 6.716 micron), whereas the gap sizes of Bioceramic material ranged from (3 to 11 micron) and it had the smallest mean gaps 1.428 micron ( Conclusion: The current study showed the rapprochement of marginal adaptation degrees of BC material and that of MTA material and the statistical analyzes showed important differences. There has been a superior behavior of Bioceramic than MTA and it adapts better with the adjacent dentin.